2016
DOI: 10.4238/gmr.15027874
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate protects retinal vascular endothelial cells from high glucose stress in vitro via the MAPK/ERK-VEGF pathway

Abstract: ABSTRACT. Diabetic retinopathy (DR) is a frequent microvascular complication of diabetes, and one of the most common causes of legal blindness in the world. Epigallocatechin-3-gallate (EGCG) produces an anti-oxidative and anti-inflammatory effect against various human diseases. In this study, we determined the effect of EGCG on a human retinal endothelial cell (HREC) line. The cell viability was determined by a standard MTT assay, while the cell cycle and apoptosis rate were analyzed by flow cytometry. Inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…(2014) Epigallocatechin gallate 20 and 40 mM Human retinal endothelial cell Inhibits expression of vascular endothelial growth factor (VEGF) and reduces negative impact of high glucose concentration on the cell viability. Prevents diabetic retinopathy Zhang et al. (2016) Epigallocatechin gallate 1–200 μM Sprague-Dawley rats Inhibits cell proliferation and reduces vascular leakage and permeability in VEGF.…”
Section: Protective Effects Of Dietary Natural Plant Products Againstmentioning
confidence: 99%
“…(2014) Epigallocatechin gallate 20 and 40 mM Human retinal endothelial cell Inhibits expression of vascular endothelial growth factor (VEGF) and reduces negative impact of high glucose concentration on the cell viability. Prevents diabetic retinopathy Zhang et al. (2016) Epigallocatechin gallate 1–200 μM Sprague-Dawley rats Inhibits cell proliferation and reduces vascular leakage and permeability in VEGF.…”
Section: Protective Effects Of Dietary Natural Plant Products Againstmentioning
confidence: 99%
“…Thus, for example, a protective effect has been observed for DR and other retinopathies with resveratrol [23][24][25], epigallocatechin gallate [26,27], curcumin [28,29] and quercetin [30,31], among others. Their actions have been attributed to their capacity to modulate different molecular targets, including sirtuins like SIRT1 [32], kinases such as MAPK [33][34][35], transcription factors like Nrf2/ARE [36,37], nuclear factor kappa B (NF-kB) [34] and others that provide antioxidant and anti-inflammatory protection [3]. We have demonstrated the protector effect of Pter as an antioxidant in different experimental models [38].…”
Section: Discussionmentioning
confidence: 94%
“…In the vitreous and retinal tissues of patients with PDR, VEGF gene, and protein expression levels are significantly increased and are closely related to retinal neovascularization [34]. Previous experiments have shown that in addition to the common cognitive VEGF AKT-inositol 1,4,5-trisphosphate pathway and PLC-γ-MAPK (including inositol 1,4,5-trisphosphate), VEGF is also involved in the expression of NF-κB and the activation of TRPC channels, regulating angiogenesis [35].…”
Section: Discussionmentioning
confidence: 99%